A simple model to assess the probability of invasion in ductal carcinoma in situ of the breast diagnosed by needle biopsy - Coufal, Oldřich; Selingerová, Iveta; Vrtělová, Pavlína; Krsička, Petr; Gabrielová, Lucie; Fabian, Pavel; Stískalová, Kateřina; Schneiderová, Monika; Poprach, Alexandr; Justan, Ivan (BioMed research international, 2014)
OBJECTIVES: The aim of the study was to develop a clinical prediction model for assessing the probability of having invasive cancer in the definitive surgical resection specimen in patients with biopsy diagnosis of ductal carcinoma in situ (DCIS) of the breast, to facilitate decision making regarding axillary surgery. METHODS: In 349 women with DCIS, predictors of invasion in the definitive resection specimen were identified. A model to predict the probability of invasion was developed and subsequently simplified to divide patients into two risk categories. The model's performance was validated on another patient population. RESULTS: Multivariate logistic regression revealed four independent predictors of invasion: (i) suspicious (micro)invasion in the biopsy specimen; (ii) visibility of the lesion on ultrasonography; (iii) size of the lesion on mammography>30 mm; (iv) clinical palpability of the lesion. The actual frequency of invasion in the high-risk patient group in the test and validation population was 52.6% and 48.3%, respectively; in the low-risk group it was 16.8% and 7.1%, respectively. CONCLUSION: The model proved to have good performance. In patients with a low probability of invasion, an axillary procedure can be omitted without a substantial risk of additional surgery.
Keywords: Models, Statistical; intraduktální neinfiltrující karcinom; nádory prsu; jehlová biopsie; statistické modely; Female; Breast Neoplasms; Carcinoma, Intraductal, Noninfiltrating; Humans; ženské pohlaví; Risk; lidé; riziko; Biopsy, Needle